No effect of acute beetroot juice ingestion on oxygen consumption, glucose kinetics, or skeletal muscle metabolism during submaximal exercise in males - Betteridge, S.; Bescós, R.; Martorell, M.; Pons, A.; Garnham, A. P.; Stathis, C. C.; McConell, G. K. (Journal of Applied Physiology, 2016)
Beetroot juice, which is rich in nitrate (NO3-), has been shown in some studies to decrease oxygen consumption (V?o2) for a given exercise workload, i.e., increasing efficiency and exercise tolerance. Few studies have examined the effect of beetroot juice or nitrate supplementation on exercise metabolism. Eight healthy recreationally active males participated in three trials involving ingestion of either beetroot juice (Beet; ~8 mmol NO3-), Placebo (nitrate-depleted Beet), or Beet + mouthwash (Beet+MW), all of which were performed in a randomized single-blind crossover design. Two-and-a-half hours later, participants cycled for 60 min on an ergometer at 65% of V?o2 peak. [6,6-2H]glucose was infused to determine glucose kinetics, blood samples obtained throughout exercise, and skeletal muscle biopsies that were obtained pre- and postexercise. Plasma nitrite [NO2-] increased significantly (~130%) with Beet, and this was attenuated in MW+Beet. Beet and Beet+MW had no significant effect on oxygen consumption, blood glucose, blood lactate, plasma nonesterified fatty acids, or plasma insulin during exercise. Beet and Beet+MW also had no significant effect on the increase in glucose disposal during exercise. In addition, Beet and Beet+MW had no significant effect on the decrease in muscle glycogen and phosphocreatine and the increase in muscle creatine, lactate, and phosphorylated acetyl CoA carboxylase during exercise. In conclusion, at the dose used, acute ingestion of beetroot juice had little effect on skeletal muscle metabolism during exercise.